Cyber Security Awareness Simulation for Web Phishing in E-Commerce - Sutanto, Jason Matthew; Nadia, Nadia (Engineering, MAthematics and Computer Science Journal (EMACS), 2025)
The development of information and communication technology has changed people's behavior in conducting transactions for buying and selling goods and services. With e-commerce, people can conduct transactions for buying and selling goods or services digitally. Although e-commerce can provide several positive impacts for society, one of which is through the ease of buying and selling goods digitally, e-commerce also has negative impacts for society, one of which is the risk of cybercrime, such as hacking, theft, and fraud. Therefore, consumers as e-commerce actors need to be protected, guarded, and secured. Protection in cyberspace is not only about strengthening the existing security system, but e-commerce users also need to be given an understanding and knowledge about cybersecurity to prevent data theft and hacking through phishing or other social engineering attacks. This study aims to build an application or feature that can increase security awareness for e-commerce users. The method used is the Waterfall method, as well as SIT (System Integration Testing) and UAT (User Acceptance Testing). Algorithm design involves the Dart programming language and the Flutter framework. The results of the study show that the applications or features created can increase security awareness among users and prevent the risk of cybercrime threats, such as fraud or hacking.